2014
DOI: 10.1017/s1466252314000255
|View full text |Cite
|
Sign up to set email alerts
|

The monster we don't see: subclinical BRD in beef cattle

Abstract: Bovine respiratory disease (BRD) is the most expensive disease affecting United States cattle. Recently weaned calves are the focus of prevention and treatment research. Identifying affected cattle early in the course of BRD is difficult. Intervention during the early stages of BRD improves treatment outcomes; however, cattle as prey animals are excellent at hiding signs of disease, especially if the caregiver has not gained their trust. Depression, appetite loss, and changes in respiratory character are the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…The economic impact of subclinical histophilosis is largely unexplored, in spite of its likely importance (Kennedy et al 1960). An experienced food animal veterinarian remarked recently, in the context of BRD complex, that subclinical disease is the monster we don't see (Griffin 2014). This is due to the practical difficulties of attempting to follow specific cohorts of cattle through slaughter for sampling and testing, and matching those findings to those in individual animals, treated and untreated at the feed yard.…”
Section: Cattlementioning
confidence: 99%
“…The economic impact of subclinical histophilosis is largely unexplored, in spite of its likely importance (Kennedy et al 1960). An experienced food animal veterinarian remarked recently, in the context of BRD complex, that subclinical disease is the monster we don't see (Griffin 2014). This is due to the practical difficulties of attempting to follow specific cohorts of cattle through slaughter for sampling and testing, and matching those findings to those in individual animals, treated and untreated at the feed yard.…”
Section: Cattlementioning
confidence: 99%
“…Bovine respiratory disease (BRD) is considered to be one of the most economically important diseases affecting feedlot cattle (Griffin, 2014). Despite attempts to reduce the morbidity and mortality of the disease through management practices and vaccination programs, little progress has been made to lower the in- ABSTRACT: Bovine respiratory disease (BRD) is an economically important disease of feedlot cattle that is caused by viral and bacterial pathogen members of the BRD complex.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike clinical BRD, the prevalence of subclinical BRD has not been well documented. However, it has been suggested that subclinical BRD infection is common, primarily because the correlation of lung lesions in harvested cattle with cattle diagnosed with BRD is low (Griffin, 2014). Common findings at harvest include lung consolidation, in which the lung alveoli are filled with fluid or tissue, and the presence of interstitial fibrinous connective tissue that can lead to fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…12 Although widely used, treatment records using DART signs are poorly correlated with post-therapeutic prognosis. 13 Accurate prognosis of BRD at the time of treatment is crucial for effective management (drug selection, sorting). To improve accuracy of diagnosis, early detection, and prognosis of BRD, new methods and technologies have been developed recently .…”
mentioning
confidence: 99%